Influence of mulching and poultry manure on wild tomato (Solanum lycopersicum var. cerasiforme (Dunal) production - Díaz-Vázquez, Felicito Ausencio; Sandoval-Rangel, Alberto (Ecosistemas y Recursos Agropecuarios, 2023)
The implementation of improvements in the production of wild tomato genotypes mproves fruit quality, although yield remains stable. The objective was to evaluate the effect of plastic mulch and the integration of poultry manure into the soil on plant growth, yield and mineral content of wild tomato fruit during the spring-summer cycle of 2022. Wild tomato plants were established in beds with white, gray, black and no mulch, with and without application of poultry manure. No statistical differences were observed between treatments for the effect of the application of poultry manure and mulch for growth and yield variables;on the contrary, the application of poultry manure generated differences(P ≤ 0.01)for total soluble solids content. Mulch application and mulch color generated differences (P ≤ 0.01) for soluble solids content,NO−3, Na+ and pH in fruit juice. The interaction of white mulch with poultry manure application exceeded the effect generated separately for soluble solids.